May Measurement Month 2018–2019: an analysis of blood pressure screening results from Austria . (7th October 2022) - Glantschnig, Theresa; Koppelstätter, Christian; Zweiker, David; Kolesnik, Ewald; Niederl, Ella; Kraler, Elisabeth; Stoff, Ingrid; Zweiker, Robert; Weber, Thomas; Horn, Sabine; Weiss, Thomas; Wang, Wei; et al.
Abstract: Arterial hypertension is a global burden leading to over 10.8 million deaths per year worldwide. May Measurement Month (MMM) is a global project initiated by the International Society of Hypertension to raise the awareness of high blood pressure (BP) in the population. Following the MMM protocol 2508 participants ≥18 years had their BP measured in Austria in MMM18 and MMM19. Of those screened, 54.6% were found to be hypertensive, defined as a BP ≥140/90 mmHg and/or being on treatment for hypertension. Among those individuals with hypertension, 56.1% were on medication but only 42.0% of those treated had controlled BP (<140/90 mmHg). Lower BPs were found in those with previous myocardial infarction (MI), probably explained by a medical monitoring system of patients with MI in Austria. Those with hypertension were referred for further medical investigations and were provided lifestyle advice. Among a high number of individuals receiving antihypertensive treatment, BP is still not controlled. Further screening and monitoring of therapeutic effects is urgently required.